A scoping review of agrochemical use in Southeast Asia: Implications to health, socioeconomic, knowledge, interventions, and policies aspects - Nguyen Cong Thanh; Unger, Fred (International Livestock Research Institute, 2024)
This scoping review aims to provide a comprehensive analysis of pesticide usage in Southeast Asia, focusing on its implications for health, socioeconomic status, knowledge gaps, interventions, and policies from 2014 to 2024. Agrochemicals, particularly pesticides, are integral to agricultural practices, yet their use is associated with significant public health risks and environmental concerns. The review synthesizes quantitative data on pesticide application trends across the region, revealing fluctuating usage patterns that vary by country and type of pesticide. Health implications include acute and chronic health risks, particularly among farmers and agricultural workers who are frequently exposed to harmful chemicals. The review highlights significant associations between pesticide exposure and adverse health outcomes, including respiratory issues, neurological damage, and mental health disorders. Furthermore, socioeconomic factors such as the economic dependence on agriculture and limited access to training exacerbate the reliance on hazardous pesticide mixtures. Knowledge gaps persist regarding safe pesticide use, with many farmers exhibiting a disconnect between awareness of risks and the adoption of protective measures. The review identifies successful interventions that promote good agricultural practices (GAP) and ecological engineering, which can mitigate pesticide dependency and enhance sustainability. Additionally, policy recommendations emphasize the necessity of stricter regulations on pesticide use, improved monitoring systems, and the promotion of biopesticides as safer alternatives. Overall, this scoping review underscores the urgent need for coordinated efforts among stakeholders to develop and implement effective strategies for managing pesticide use in Southeast Asia. By fostering a comprehensive understanding of the complexities surrounding agrochemical application, the review aims to guide future research, inform policy-making, and contribute to healthier, more sustainable agricultural practices in the region.